Transcriptome Profiling of Human Monocyte-Derived Macrophages Upon CCL2 Neutralization Reveals an Association Between Activation of Innate Immune Pathways and Restriction of HIV-1 Gene Expression - Covino, Daniela Angela; Kaczor-Urbanowicz, Karolina Elżbieta; Lu, Jing; Chiantore, Maria Vincenza; Fiorucci, Gianna; Vescio, Maria Fenicia; Catapano, Laura; Purificato, Cristina; Galluzzo, Clementina Maria; Amici, Roberta; Andreotti, Mauro; Gauzzi, Maria Cristina; et al. (Frontiers in Immunology, 2020)
Macrophages are key targets of human immunodeficiency virus type 1 (HIV-1) infection and main producers of the proinflammatory chemokine CC chemokine ligand 2 (CCL2), whose expression is induced by HIV-1 both in vitro and in vivo. We previously found that CCL2 neutralization in monocyte-derived macrophages (MDMs) strongly inhibited HIV-1 replication affecting post-entry steps of the viral life cycle. Here, we used RNA-sequencing to deeply characterize the cellular factors and pathways modulated by CCL2 blocking in MDMs and involved in HIV-1 replication restriction. We report that exposure to CCL2 neutralizing antibody profoundly affected the MDM transcriptome. Functional annotation clustering of up-regulated genes identified two clusters enriched for antiviral defense and immune response pathways, comprising several interferon-stimulated, and restriction factor coding genes. Transcripts in the clusters were enriched for RELA and NFKB1 targets, suggesting the activation of the canonical nuclear factor κB pathway as part of a regulatory network involving miR-155 up-regulation. Furthermore, while HIV-1 infection caused small changes to the MDM transcriptome, with no evidence of host defense gene expression and type I interferon signature, CCL2 blocking enabled the activation of a strong host innate response in infected macrophage cultures, and potently inhibited viral genes expression. Notably, an inverse correlation was found between levels of viral transcripts and of the restriction factors APOBEC3A (apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3 A), ISG15, and MX1. These findings highlight an association between activation of innate immune pathways and HIV-1 restriction upon CCL2 blocking and identify this chemokine as an endogenous factor contributing to the defective macrophage response to HIV-1. Therapeutic targeting of CCL2 may thus strengthen host innate immunity and restrict HIV-1 replication.